2006
DOI: 10.1002/chem.200600698
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent PtII(bipyridyl)(diacetylide) Chromophores with Pendant Binding Sites as Energy Donors for Sensitised Near‐Infrared Emission from Lanthanides: Structures and Photophysics of PtII/LnIII Assemblies

Abstract: The complexes [Pt(bipy){CC-(4-pyridyl)}(2)] (1) and [Pt(tBu(2)bipy){CC-(4-pyridyl)}(2)] (2) and [Pt(tBu(2)-bipy)(CC-phen)(2)] (3) all contain a Pt(bipy)(diacetylide) core with pendant 4-pyridyl (1 and 2) or phenanthroline (3) units which can be coordinated to {Ln(diketonate)(3)} fragments (Ln = a lanthanide) to make covalently-linked Pt(II)/Ln(III) polynuclear assemblies in which the Pt(II) chromophore, absorbing in the visible region, can be used to sensitise near-infrared luminescence from the Ln(III) centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(47 citation statements)
references
References 78 publications
2
44
0
1
Order By: Relevance
“…[51] Complex 3 was prepared according to the literature procedure. [62] CD 3 CN was used for NMR experiments, owing to the good solubility of the trimetallic complexes 4a-c in this solvent. CH 2 Cl 2 was used for photophysical studies to allow better comparison to other photoluminescence experiments we have reported on cationic isocyanide-bound cyclometalated iridium complexes [52,53] and closely-related analogues of platinum complex 3, [59] all of which were conducted in CH 2 Cl 2 solvent.…”
Section: Experimental Section Materialsmentioning
confidence: 99%
“…[51] Complex 3 was prepared according to the literature procedure. [62] CD 3 CN was used for NMR experiments, owing to the good solubility of the trimetallic complexes 4a-c in this solvent. CH 2 Cl 2 was used for photophysical studies to allow better comparison to other photoluminescence experiments we have reported on cationic isocyanide-bound cyclometalated iridium complexes [52,53] and closely-related analogues of platinum complex 3, [59] all of which were conducted in CH 2 Cl 2 solvent.…”
Section: Experimental Section Materialsmentioning
confidence: 99%
“…Nonetheless, a variety of Pt(II) polypyridyl luminophores have been used successfully in a range of d--f systems, including heterometallic complexes, 6--8 coordination polymers, 9 and supramolecular systems. 10--12 Interestingly then, despite the myriad of Pt(II) polypyridyl--based antennae which have been reported, to the best of our knowledge only two examples of cyclometalated arylpolypyridyl Pt(II) d--f complexes 13,14 have been demonstrated to show sensitised Ln(III) emission.…”
Section: --5mentioning
confidence: 99%
“…As the model complex Eu(hfac) 3 (bpyC"C) lacks of intensity at k > 350 nm in the excitation spectrum (Fig. S11, Supplementary material), the sensitized lanthanide emission of Pt-Ln heteronuclear complexes should originate from energy transfer from the platinum(II) terpyridyl alkynyl antenna chromophore [10][11][12][13][14][15][16].…”
Section: Luminescence Propertiesmentioning
confidence: 99%
“…The entire quenching of Pt-based luminescence in these Pt-Ln complexes except for 7 in solid state together with the observation of sensitized lanthanide luminescence with excitation at the absorption region of Pt-based chromophore reveals unambiguously that quite effective Pt ? Ln energy transfer is operating in these Pt-Ln heteronuclear complexes [9][10][11][12][13][14][15][16].…”
Section: Luminescence Propertiesmentioning
confidence: 99%
See 1 more Smart Citation